Long-term effectiveness of radiofrequency renal denervation in patients with resistant arterial hypertension (10-year follow-up results) - O.L. Rekovets; Yu.M. Sirenko; O.O. Torbas; S.M. Kushnir; G.F. Prymak (Кардіохірургія та інтервенційна кардіологія)
The aim – to determine the long-term efficacy and safety of renal denervation (RDN) at 10-year follow-up. Materials and methods. We selected 1146 patients with resistant arterial hypertension (RAH) who received 3 or more antihypertensive drugs. 16 patients were selected for renal artery denervation. RDN was performed in 8 patients (0.70 %). 8 patients refused the procedure. The age was 52.13 ± 3.88 years (40–66), the duration of hypertension was 16.75 ± 2.17 (12–25) years. The number of antihypertensive drugs was 5.5 ± 0.18. Office SBP/DBP on optimization of therapy in patients was 156.88/95.00 ± 2.98 mm Hg and heart rate – 68.88 ± 3.28 beats/min. 24SBP/DBP was 149.16 ± 5.40/86.98 ± 5.08 mm Hg. 24HR was 70.12 ± 2.94 beats/min. All patients tolerated the procedure well. Results and discussion. The decrease in office SBP/DBP was –12.59/–10.0 mm Hg; –11.17/–2.57 mm Hg; –20.31/–11.71 mm Hg, –27.71/–13.33 mm Hg and –30.21/–16.67 mm Hg, in the dynamics of 1 month, 12 months, 2 years, 5 years and 10 years, respectively, p <0.05 for all values compared to the initial. The office heart rate at the stages of 1 month, 6, 12 months, 2 years, 5 and 10 years decreased, its dynamics were –3.74 bpm, –4.68 bpm, –1.45 bpm, –2.13 bpm, –4.21 bpm, –3.88 bpm, respectively. The decrease in 24SBP/DBP was –14.45/–6.95 mmHg, –8.70/–10.01 mm Hg, –19.45/–12.37 mm Hg, –19.91/–11.24 mm Hg, –29.93/–13.61 mm Hg. and –26.13/–23.35 mm Hg (p<0.05 for all values). 24HR dynamics: –3.16 bpm, – 4.19 bpm, + 1.43 bpm, –1.51 bpm, –4.46 bpm, and –5.49 bpm, respectively. After 2, 5, and 10 years, all patients reached the target blood pressure level both in the office and with ABPM. Patients reduced the number of antihypertensive drugs from 5.50 ± 0.18 to 3.50 ± 0.30 – after 5 years and 3.67 ± 0.18 – after 10 years after RDN. GFR practically did not change over 10 years from 76.10 ± 5.62 to 64.60 ± 1.93 ml/min/1.73m2, p>0.05. One patient died of thyroid cancer 2 years later. All other patients are alive and have not had any cardiovascular event or death during 10 years. Conclusion. Long-term results of renal artery denervation showed no cases of cardiovascular events, development of diabetes or cardiovascular death over 10 years. RDN contributed to a reduction in the number of antihypertensive drugs from 5.5 to 3.67 after 10 years of therapy against the background of 100 % achievement of the target BP level.